INNOVATION AND TEACHERS’ IN SERVICE EDUCATION: THE CULTURE BASED APPROACH - Angeloni, Grazia (European Scientific Journal, ESJ, 2013)
In the text presented below the two key words: innovation and teachers’ in-service education are structured in terms of relationship and are included in the current global scenario that sees not just Italian, but each school in any foreign country committed to interface with new and complex problems. It is also argued the implications of them, on an application field, where the theoretical and praxical dimensions receive mediation and which supports the suggestion of a cultural approach to the teachers’ in-service education.